Study about Physiological Benefit of Intermittent Fasting - Mishra , Amiyakanta; Ray , Biswaranjan (Advanced Concepts in Medicine and Medical Research Vol. 5, 2023)
This chapter aimed to focus on different aspects of Intermittent Fasting and its physiological benefit. Intermittent fasting is an eating plan that switches between fasting and eating on a regular schedule. It is a type of Popular Dietary Pattern of Practice which is based on Timed Periods of Fasting. Intermittent fasting works by prolonging the period when your body has burned through the calories consumed during your last meal and begins burning fat. Time-restricted eating and alternate-day fasting are two distinct regimens. Despite the lack of significant randomized control trials examining the connection between CVS result and intermittent fasting, recent research indicates that diet restriction is beneficial to overall health. Some Study suggest that alternate day fasting is about as effective as a typical low calori diet for weight loss. Intermittent fasting is safe for many people but it is not for everyone.